Implementation of the School Literacy Movement at SMP Negeri 1 Talang Ubi, Indonesia - Hartaty, Nani; Fitria, Happy; Wahidy, Achmad (Journal of Social Work and Science Education, 2022)
The goal of this paper was to look at how the school literacy movement was being implemented in SMP Negeri 1 Talang Ubi. This research takes a qualitative method, including interview, observation, and documentation as tools. The gathered data were then examined using Miles and Huberman's hypothesis. According to the study's findings, the preparation for the implementation of the School Literacy Movement at SMP Negeri 1 Talang Ubi was adequate in terms of building preparation, library administration, and the acquisition of reading books. However, school residents' preparation and public participation have not been emphasized. As a result, the education office must play a more active role in socialization and counseling.